Mastering System Resilience: Building Robust Software with Break-Point Testing - Ramdoss, Vasudevan Senathi (Eastasouth Institute, 2024)
Modern digital environments require software systems to efficiently manage high traffic loads and stress conditions. Through break-point testing which is dedicated performance testing you can find out the highest load your system can manage before experiencing failure or performance decline. This tutorial focuses on break-point testing with Apache JMeter which stands as an open-source performance testing application that is extensively adopted. The guide explains how to establish tests, adjust JMeter settings for precision and construct practical testing models. The guide will teach you how to identify system bottlenecks and analyze test results while optimizing performance. You will possess a definitive plan to maintain your software's reliability and scalability when exposed to stress.